PEDAGOGICAL POSSIBILITIES OF INDEPENDENT WORK IN DEVELOPMENT OF NON-STANDARD THINKING (Scientific journal of the Fergana State University, 2023)
This article is a scientific and methodical analysis of the current situation, existing problems and shortcomings, issues related to the solution of creative and non-standard thinking and lessons among students in the educational institutions of our country. Approaches, recommendations regarding the use of non-standard and creative thinking in the lessons were put forward based on foreign and local experience. Based on the analysis of the studied situations, proposals were put forward to respond to the level of thinking and thinking of students and improve their skills.